Being in the Frontline of a Sámi Culture and a Private Business: Cross-Border Reindeer Herding in Northern Norway and Sweden. (11th November 2011) - Koch, Peter; Miggelbrink, Judith
Abstract : This article investigates a conflict that loomed over the mutual use of pastures on either side of the border by various Sámi groups during the last decade. On the basis of a critical reading of Foucault, we analyse the identifications connected to different kinds of spaces that come up in the mediation of this conflict. Surprisingly, the notion of belonging to an indigenous people plays only a very limited role in this conflict. Being a Sámi and a state citizen turns out to be more important. Reindeer pastures are perceived as lands, bounded spaces, and as part of the state space, since reindeer herding is a 'nationalised' business. However, pastures as concrete places in themselves have not emerged as an important aspect of this conflict.